2010
DOI: 10.1177/1525740109353937
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Narrative-Based Language Intervention With Children Who Have Language Impairment

Abstract: This systematic review focuses on research articles published since 1980 that assess outcomes of narrative-based language intervention for preschool and school-age children with language impairment. The author conducted a comprehensive search of electronic databases and hand searches of other sources for studies using all research designs except nonexperimental case studies. The results of the studies were converted to a common metric using effect sizes. The review yielded nine studies that met inclusion crite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
75
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(82 citation statements)
references
References 25 publications
3
75
0
4
Order By: Relevance
“…Η αξιολόγηση του αφηγημα-τικού λόγου συχνά συντελεί στη διάκριση των τυπικά αναπτυσσόμενων μαθητών από εκεί-νους με γλωσσικές δυσκολίες (Vandewalle, Boets, Boons, Ghesquiere, & Zink, 2012· Westerveld et al, 2008. Επίσης, η ικανότητα παραγωγής δομημένων αφηγήσεων αποτελεί ένα νατουραλιστικό μέσο εξέτασης συγκεκριμένων γλωσσικών δεξιοτήτων (Petersen, 2010).…”
Section: η ανάλυση και η αξιολόγηση της αφήγησηςunclassified
“…Η αξιολόγηση του αφηγημα-τικού λόγου συχνά συντελεί στη διάκριση των τυπικά αναπτυσσόμενων μαθητών από εκεί-νους με γλωσσικές δυσκολίες (Vandewalle, Boets, Boons, Ghesquiere, & Zink, 2012· Westerveld et al, 2008. Επίσης, η ικανότητα παραγωγής δομημένων αφηγήσεων αποτελεί ένα νατουραλιστικό μέσο εξέτασης συγκεκριμένων γλωσσικών δεξιοτήτων (Petersen, 2010).…”
Section: η ανάλυση και η αξιολόγηση της αφήγησηςunclassified
“…These reviews have included a variety of interventions targeting various domains of language. Other reviews have had a narrow focus, evaluating multicomponent interventions for areas such as school-age grammar (Ebbels, 2014), narrative (Petersen, 2011), or auditory processing skills (Fey et al, 2011). Although these types of reviews provide valuable information, because they combine different interventions or include multicomponent interventions, they do not allow for a determination of the efficacy of a particular intervention technique.…”
Section: Discussionmentioning
confidence: 97%
“…In contrast, a modest number of studies have evaluated narrative interventions for individuals with language-learning difficulties or disorders. Such studies have revealed positive outcomes, particularly for macrostructural measures (Petersen 2011), and could serve as a resource for practitioners working with DS as well.…”
Section: Gaps In the Literature And Future Directionsmentioning
confidence: 98%